(untitled) (Marketing Journal, 2026)
This article provides a comprehensive scientific analysis of the theoretical content and practical significance of the concept of economic potential in the activities of chemical industry enterprises. Within the framework of the study, economic potential is substantiated as an important economic category that reflects the level of resource provision, production capacities, financial stability, innovative capabilities, and adaptability of industrial enterprises to market conditions. The role of economic potential in ensuring the competitiveness, investment attractiveness, and sustainable № 1 -SON YANVA R, 202 6-YIL 396 development of chemical industry enterprises is also revealed. The article scientifically substantiates that the effective utilization of economic potential is a strategic factor in enhancing the performance of enterprises.